Strategic Management in Improving the Performance of Islamic Boarding School-Based Higher Education Organizations - Supriyanto Supriyanto; Agus Zaenul Fitri; Teguh Teguh (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Islamic boarding school-based universities are often considered unable to compete with universities from outside Islamic boarding schools. The industrial revolution 4.0 towards the era of society 5.0 is characterized by a society's life integrated with technological systems in the form of IoT (Internet of Things) and AI (Artificial Intelligence) and based on robotization and automation is considered by society as an inevitable demand of the times, but difficult to achieve by studying at Islamic boarding school-based universities. At the Islamic University of Tribakti Lirboyo Kediri and the University of Islamic Boarding School Darul Ulum Jombang always strive to compete and become universities that are in demand by many people. This study uses a qualitative approach, with a multi-site study design. Data collection techniques used in-depth interviews, participant observation, and documentation. Data analysis techniques used condensation, data display, and conclusion drawing. The results of this study are strategic management applied to both institutions using SWOT analysis to identify organizational strengths and weaknesses, identify opportunities and threats, to stay ahead of market trends. Formulating strategies so that institutions are able to determine direction, deploy institutional resources to achieve goals. Implementing long-term strategies, helping institutions adapt, creating effective and efficient organizational performance, and developing product or service innovations. Evaluating strategies to ensure efficient resource utilization and adaptability to market and business changes. The implementation of strategic management at the corporate (rectorate), business unit (dean's office), and functional (study program) levels provides a solution to technological change and uncertain political, social, and cultural developments. Improving organizational performance in a structured, systematic, and massive manner will enable the university to excel at the national and even international levels, leading to a world-class Islamic university (World Class Islamic University).